Rearing characteristics of fattening Hanwoo steers managed in different stocking densities - Jae Jung Ha; Ka Young Yang; Dong Yep Oh; Jun Koo Yi; Jong Joo Kim (Asian-Australasian Journal of Animal Sciences, 2018)
Objective This study was conducted to analyze the effects of stocking density on growth and carcass quality, and behavior of Hanwoo cattle to conform with global trends, targeting animal welfare production through the practice of environmentally friendly condition. Methods Thirty six steers were randomly assigned to three treatment groups (C: 5 heads, T1: 4 heads, T2: 3 heads) and reared in separate pens with a constant stocking density of 50 m2 (C: 10 m2/head, T1: 12.5 m2/head, T2: 16.67 m2/head) per group from 12 to 30 month of age. Growth performance, behavior and carcass quality traits of each steer were recorded and compared between the treatment groups. Results In general, the average daily gain during the fattening period was lower in group T2 than in T1 and the control groups. However, carcass weight and dressing percentage was lower in the control group than in T1 or T2 groups (p<0.05). Also, marbling score at 30 months of age was the lowest in the control group (p<0.05), while the three heads group (T2) had the greatest longissimus muscle area and marbling score (p<0.05). The behavior of walking time was the greatest in T2 group, while self-grooming and fighting occurred with the most frequency in the control group (p<0.05). Conclusion Our results show that the steers in more spacious stocking density had better carcass quality and wellbeing related behaviors, indicating that a lower density has a positive effect on raising management and carcass quality. Thus it is a need to install appropriate pens fitted to welfare-oriented management practices from growing to fattening period in Hanwoo cattle.